Construction of virtual mulch film model based on discrete element method and simulation of its physical mechanical properties - Guo, Wensong; Hu, Can; He, Xiaowei; Wang, Long; Hou, Shulin; Wang, Xufeng (International Journal of Agricultural and Biological Engineering, 2020)
In China, especially in Xinjiang Region, mulch film remaining in the soil has severely jeopardized the safety of soil resources. To numerically simulate the residual film-soil-recovery implementation system, a virtual mulch film model with consistent physical and mechanical properties with real mulch film needs to be established. In this study, a flexible deformable virtual mulch film model was constructed using YADE software based on the Minkowski Sum principle and the ball-ball force-displacement constitutive rule, as well as the contact failure rule were established. The deformation behaviors of cylinders and PFacet elements, such as stretching, bending, and torsion, were described. By splicing the basic PFacet elements, a virtual mulch model was established. The mechanical model of a virtual mulch film under tension was established and the axial tensile stiffness coefficient kn was determined to be 43.30 N·m. To verify the physical and mechanical properties of this virtual mulch film, both real and virtual stretching and tearing tests were conducted. The experimental results showed that: in the process of stretching and tearing of real and virtual films, the properties of morphological features of both are basically identical; however, they clearly differ in force-displacement. The viscoelastic constitutive model between balls and yield judgment conditions requires further study. Keywords: discrete element method, mulching film, physical and mechanical properties, virtual test DOI: 10.25165/j.ijabe.20201304.5525 Citation: Guo W S, Hu C, He X W, Wang L, Hou S L, Wang X F. Construction of virtual mulch film model based on discrete element method and simulation of its physical mechanical properties. Int J Agric & Biol Eng, 2020; 13(4): 211–218.